1969
DOI: 10.1002/ar.1091640309
|View full text |Cite
|
Sign up to set email alerts
|

Spermatogenesis in the rabbit following ligation of the epididymidis at different levels

Abstract: Ligatures were placed unilaterally on the ductus deferens (experiment l ) , on the ductus deferens and the middle of the corpus epididymidis (experiment 2) and on the ductus deferens, corpus epididymidis and ductuli efferentes (experiment 3) in 39 r,abbits. The untreated contralateral side served as a control. Vasectomy alone appeared to have no effect upon the testes, or upon spermatozoa accumulated during a period of 12 weeks proximal to the ligature. In experiment 2 severe disruption of spermatogenesis occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1969
1969
1999
1999

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…Similarly, adult Wistar rats that had received an epididymectomy showed varying degrees of testicular changes which progressed to extreme degeneration of the seminiferous epithelium (Soler et al, 1990). Likewise, extensive damage to the seminiferous epithelium was observed in dogs after ligation of the cauda epididymidis (Vare and Bansal, 1974), although epididymal ligation was reported to result in temporary testicular changes followed by evidence of recovery in the rabbit (Paufler and Foote, 1969) and mouse (Baillie, 1962). As might be expected, the more proximal the site of epididymal obstruction, the greater the likelihood of testicular changes in rats (Macmillan, 1953;Harrison and Macmillan, 1954) and mice (Baillie, 1962).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, adult Wistar rats that had received an epididymectomy showed varying degrees of testicular changes which progressed to extreme degeneration of the seminiferous epithelium (Soler et al, 1990). Likewise, extensive damage to the seminiferous epithelium was observed in dogs after ligation of the cauda epididymidis (Vare and Bansal, 1974), although epididymal ligation was reported to result in temporary testicular changes followed by evidence of recovery in the rabbit (Paufler and Foote, 1969) and mouse (Baillie, 1962). As might be expected, the more proximal the site of epididymal obstruction, the greater the likelihood of testicular changes in rats (Macmillan, 1953;Harrison and Macmillan, 1954) and mice (Baillie, 1962).…”
Section: Discussionmentioning
confidence: 99%
“…Effects on the testis of epididymal obstruction in adults (usually unilateral) have varied, with some authors reporting substantial testicular damage (Harrison and Macmillan, 1954;Vare and Bansal, 1974), while others have observed that deleterious changes are followed by recovery (Baillie, 1962;Paufler and Foote, 1969). Among the possible mechanisms of testicular damage after epididymal obstruction are increased pressure in the seminiferous tubules (Vare and Bansal, 1974;Paufler and Foote, 1969), accumulation of metabolites (Pilsworth et al, 1981), and absence of substances secreted by the epididymis (Paufler and Foote, 1969;Soler et al, 1990). However, since antisperm autoantibodies rise after epididymal obstruction (Flickinger et al, 1998), an autoimmune reaction may also cause testicular changes.…”
mentioning
confidence: 99%
“…Whether or not vasectomy significantly interferes with normal testicular function has been one of the important questions in the area. There are reports of testicular function being seriously altered after vasectomy (Sackler, Weltman, Pandhi & Schwartz, 1973;Alexander, 1973; Kothari & Mishra, 1973), but there is evidence from a variety of primate and non-primate species which supports the concept that, in general, spermatogenesis continues in vasectomized males (Skinner & Rowson, 1968;Paufler & Foote, 1969;Flickinger, 1972;Vare & Bansal, 1973;Howards, Jessee & Johnson, 1975). Even in vasectomized males with persistent spermatogenesis, however, there are often signs of some alteration or impairment of the spermatogenic process (MacMillan, Desjardins, Kirton & Hafs, 1968;Igboeli & Rakha, 1970;Alexander, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…11). Disruption of spermatogenesis ( 15) prevented a resupply of sperm until effective renewal of spermatogenesis was noted at 12 weeks. Ligatures on the ductuli efferentes, in Expt.…”
Section: Sperm Retention and Resorptionmentioning
confidence: 99%
“…Atrophy of the testes has been observed in males vasectomized for several years ( 15). Thus, reduced spermatogenesis also may account for some of the difference.…”
Section: Sperm Retention and Resorptionmentioning
confidence: 99%